2017
DOI: 10.3390/f8040105
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Thinning on Tree Growth and Stand Structure of White Birch (Betula platyphylla Sukaczev) and Siberian Larch (Larix sibirica Ledeb.) in Mongolia

Abstract: The forests of North Mongolia are largely dominated either by larch (Larix sibirica Ledeb.) or birch (Betula platyphylla Sukaczev). The increasing demand for timber and firewood is currently met by removal of wood from these forest stands. Therefore, silvicultural approaches that account for both utilization and protection are needed. Thinning trials were established in the research area Altansumber, in the mountain forest steppe west of the town of Darkhan. We analyzed the response of non-spatial and spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…Already in the second half of the 20th century, research trials for the evaluation of logging impact concluded that in Mongolia the impact of selective logging is ecologically more positive than clearcutting (Savin et al 1988). The shortterm effects of thinning from below on individual tree growth was recently studied in larch and birch stands near the steppe border (Gradel et al 2017c). The authors found that the growth response of the remaining trees was significantly positive and directly related to the reduction of surrounding competitor trees.…”
Section: Logging -Scale and Practicesmentioning
confidence: 99%
“…Already in the second half of the 20th century, research trials for the evaluation of logging impact concluded that in Mongolia the impact of selective logging is ecologically more positive than clearcutting (Savin et al 1988). The shortterm effects of thinning from below on individual tree growth was recently studied in larch and birch stands near the steppe border (Gradel et al 2017c). The authors found that the growth response of the remaining trees was significantly positive and directly related to the reduction of surrounding competitor trees.…”
Section: Logging -Scale and Practicesmentioning
confidence: 99%
“…Land cover changes in the region are related to both climate change Miao et al 2015) as well as anthropogenic impacts related to urbanization (Allington et al 2017;Fan et al 2016), livestock herding (Allington et al 2017, Sternberg 2012, mining (Batbayar et al 2019;Jarsjö et al 2017) and logging (Batkhuu et al 2011;Tsogtbaatar 2004). In vast parts of the Mongolian Plateau, forest degradation and losses (Gradel et al 2017;Juřička et al 2019a) as well as desertification of grasslands (Khodolmor et al 2013;Wei et al 2019) have modified a natural land cover. The key drivers of these processes are mining, agriculture / urbanization and deforestation, which are at the same time major water users and polluters (Batbayar et al 2019;Jarsjö et al 2017;Karthe et al 2017).…”
mentioning
confidence: 99%
“…To gain a better understanding of the character of the different treatments, we analyzed the type and intensity of the logging events [45,46] carried out in February 1998. We assessed the selective logging weight (originally referred to as the thinning weight, or "rG ratio"; [47]), which represents the intensity of the selective logging.…”
Section: Non-spatial Analysis Of the Harvest Events In 1998mentioning
confidence: 99%
“…We compared relevant stand measures and index values [46] directly before and after the harvest events in order to better quantify potential changes in diameter size classes and forest structure caused by the logging event. We analyzed the following variables: basal area (m 2 ), diameter coefficient of variation (CV; also denoted as DBH-differentiation [49]), quadratic mean diameter of all trees (Dg), arithmetic mean diameter of all trees (D), quadratic mean diameter of the 200 strongest trees (Dg_200), and the arithmetic mean diameter of the 200 strongest trees (D_200).…”
Section: Non-spatial Analysis Of the Harvest Events In 1998mentioning
confidence: 99%
See 1 more Smart Citation